VALVULAR BRONCHIAL CLOSURE IN THE TREATMENT OF BRONCHOPLEURAL FISTULAS - E. A. Drobyazgin (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Aim of the study: the use of the valvular bronchial blocking technique in the treatment of bronchopleural fistulas in patients with thoracic pathology. Material and methods. During the period from 2012 to 2017, the valvular bronchial blocking technique was used in the treatment of 76 patients with bronchopleural fistulae (men 68, women 8). The age of patients is 16 to 82 years. In 24 patients, the indication for bronchial blocking was complications of thoracoscopic operations with bullous pulmonary emphysema. In a smaller number of cases (21), pneumothorax occurred in patients with COPD. Purulent diseases of the lungs and pleura caused a blockage in 24 patients. Results. Medlung blockers were used to treat patients. The blocker was placed in the "targeted" bronchus under local anesthesia while performing fibroblochoscopy. In all cases, the blocker was established. Reduction or cessation of air leakage through drainage from the pleural cavity occurred within a period of 5 hours to 1.5 days. In patients with poorly positive dynamics, correction of the blocker standing and additional blocking were performed, which resulted in good outcomes in 4 patients. A positive result was obtained in more than 85 % of patients. In 10 cases, no effect was obtained, which required surgical intervention. The duration of the blocker in the bronchus was from 4 days to 4 months. When removing the blocker, there were no complications. Conclusion. The technique of valvular bronchial blocking allowed to improve the results of treatment of patients with thoracic profile with various diseases complicated by the appearance of bronchopleural fistula, including complications of the postoperative period.